Falsafah Ekonomi dan Instrumen Muamalah dalam Amalan Perbankan Islam di Malaysia - Borhan, Joni Tamkin (Jurnal Usuluddin, 2001)
Islamic banking is the conduct of banking operations in line with Islamic principles of muamalat. The main principles of Islamic banking activities comprise of prohibition of riba in all forms of transactions, undertaking business and trade activities on the basis of profit sharing and for the benefit of society and development of all halal aspects of business that are not prohibited by Islam. This article will discuss the principles of philosophical Economics of Islamic banking system which will show us the identity and distinctions between riba banking and Islamic banking. The modes of operations of the Malaysian Islamic banking system based on muamalat will also be discussed.